A Trust Management System Through Ambient Communication for VANET - Amel Ltifi; Ahmed Zouinkhi (International Journal of Informatics and Communication Technology (IJ-ICT), 2013)
In a VANET, the network topology is constantly changing. In fact, it requires distributed self-organizing security systems. In this article, we propose a distributed self-organizing trust management system for vehicular ad-hoc networks (VANETs), given the disastrous consequences of acting on false information sent by the malicious peers in this context. Our application can verify the correctness of alert messages sent by other vehicles about road accident. We opted to apply ambient communication technology to provide a self-organized network. We introduce the concept of “ambient intelligent vehicle” that consists in integrating ambient intelligence features in VANET. Vehicles are considered as intelligent agents that communicate in an ambient environment. Such vehicles are able to control and to detect false warning based on trust management system depicted in this article. Vehicles are arranged into clusters in order to facilitate communication and to reduce overhead. We model how vehicle operate using UML state diagram.DOI: http://dx.doi.org/10.11591/ij-ict.v2i2.2980